2020
DOI: 10.3389/fimmu.2020.00301
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Vitamin D-Mediated Hypercalcemia as a Potential Risk Factor in Central Nervous System Demyelinating Disease

Abstract: The exact cause of multiple sclerosis (MS) is unknown; however, it is considered to be an inflammatory disease of the central nervous system (CNS) triggered by a combination of both environmental and genetic factors. Vitamin D deficiency is also discussed as a possible disease-promoting factor in MS, as low vitamin D status is associated with increased formation of CNS lesions, elevated number of relapses and accelerated disease progression. However, it remains unclear whether this association is causal and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
(68 reference statements)
0
7
0
1
Order By: Relevance
“…However, CA concentration is positively correlated with inflammation. Some studies showed that hypercalcemia is linked with inflammatory diseases (27,28). Some crucial inflammatory cytokines, such as IL-6, IL-1β, can upregulate the CA-sensing receptor, which can control blood CA homeostasis and is a promoter and responder of inflammation (24,29).…”
Section: Discussionmentioning
confidence: 99%
“…However, CA concentration is positively correlated with inflammation. Some studies showed that hypercalcemia is linked with inflammatory diseases (27,28). Some crucial inflammatory cytokines, such as IL-6, IL-1β, can upregulate the CA-sensing receptor, which can control blood CA homeostasis and is a promoter and responder of inflammation (24,29).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, some authors have raised the possibility that VitD excess could trigger inflammation through T-cell stimulation via hypercalcemia. In this sense, serum calcium levels and body weight loss have been frequently employed to indicate VitD toxicity [ 72 , 73 ]. In healthy individuals, exogenous VitD toxicity is generally associated with the continuous use of high VitD doses [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, among the clinical manifestations, changes in the level of consciousness are one of the most common symptoms of vitamin D in high-doses associated hypercalcemia, especially when serum levels are greater than 13 mg/dL. In this case, the individual usually progresses to lethargy, mental confusion with probable outcomes to the state of coma or seizures ( 40 , 41 ). There are numerous reports of encephalopathy/coma in hypercalcemic patients and this is closely related to a delta–theta activity pattern ( 42 ).…”
Section: Discussionmentioning
confidence: 99%